Scoping Review: Involvement of Parents of Children with Special Needs in Home Based Education During the Covid-19 Pandemic - Siti Dini Fakhriya; Tsurayya Syarif Zain (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
During the Covid-19 pandemic the learning process shifted from school-based education to home-based education, so parents need to be involved in children's learning in schools especially on home-based learning systems. The transition of this learning process involves parents to add roles and involvement especially parents with children with special needs. This study is a literary study using the scooping review method. Scooping reviews are used in this study to find out the involvement of parents with children with special needs in home-based education. A scoping review is structured based on a framework by Arksey and O'Malley (2005) that consists of five stages namely identifying research questions, identifying relevant studies, selecting data mapping studies, compiling, summarizing, and reporting results. The study search was conducted through several databases such as Science Direct, sage publications, and Proquest and 8 articles met the criteria. Eight studies were used, consisting of six qualitative studies, one quantitative study, and one mixed-method study. The study came from several countries such as Indonesia, Filipina, Mexico, Germany, Israel, Zimbabwe, Spain, Turkey, and the USA. The results of the research show that there are three identified themes: as a teacher, as a therapist, and as a search for information. In this case, parents with children with special needs need to work with professionals to maximize learning at school or home.Selama pandemic covid-19 proses pembelajaran beralih dari school-based education menjadi home based education, sehingga orang tua perlu terlibat dalam pembelajaran anak di sekolah terutama pada sistem pembelajaran berbasis rumah. Peralihan proses pembelajaran ini, menutun orang tua untuk menambah peran dan keterlibatan khususnya orang tua dengan anak berkebutuhan khusus. Penelitian ini merupakan studi literatur dengan metode scoping review. Scoping review digunakan dalam penelitian ini untuk mengetahui bagaimana keterlibatan orang tua dengan anak berkebutuhan khusus dalam home based education. Scoping review disusun berdasarkan kerangka oleh Arksey dan O’Malley (2005) yang terdiri atas 5 tahap yaitu identifikasi pertanyaan penelitian, identifkasi studi yang revelan, pemilihan studi pemetaan data, menyusun, meringkas dan melaporkan hasil. Pencarian studi dilakukan melalui beberapa database seperti science direct, sage publication dan proquest dan terdapat 8 artikel yang memenuhi kriteria. Adapun 8 studi digunakan yang terdiri dari 6 studi kualitatif, 1 studi kuantitatif dan 1 studi menggunakan mixed method. Studi tersebut berasal dari beberapa negara seperti, Indonesia, Filpina, Mexico, German, Israel, Zimbabwe, Spanyol, Turki dan USA.Hasil penelitian menunjukkan terdapat 3 tema yang teridentifikasi yaitu, sebagai pengajar, sebagai therapist dan pencarian informasi. Dalam hal ini orang tua dengan anak berkebutuhan khusus perlu bekerja sama dengan professional untuk dapat memaksimalkan pembelajaran di sekolah atau dirumah.